Integrating DNA methylation and hydroxymethylation data with the mint pipeline - Cavalcante, Raymond G. (Cancer Res, 2017)
DNA methylation (5mC) plays important roles in mammalian development, oncogenesis, treatment response, and responses to the environment. DNA hydroxymethylation (5hmC) is also an informative epigenetic mark with distinct roles in regulation and cancer. Gold-standard, widely used technologies (bisulfite-conversion followed by deep sequencing) cannot distinguish between 5mC and 5hmC. Therefore, additional experiments are required to differentiate the two marks, and in silico methods are needed to analyze, integrate, and interpret these data. We developed the Methylation INTegration (mint) pipeline to support the comprehensive analysis of bisulfite-conversion (BS) and immunoprecipitation (IP) based methylation and hydroxymethylation assays, with additional steps towards integration, visualization and interpretation. The pipeline is available as both a command line and a Galaxy graphical user interface (GUI) tool. Both implementations require minimal configuration while remaining flexible to experiment specific needs.